2001
DOI: 10.3758/bf03196216
|View full text |Cite
|
Sign up to set email alerts
|

Infants attend to second-order relational properties of faces

Abstract: Two experiments investigated whether 7-month-old infants attend to the spatial distance measurements relating internal features of the human face. A visual preference paradigm was used, in which two versions of the same female face (one either lengthened or shortened, and one nonmodified) were presented simultaneously. In Experiment 1, infants looked longer at the nonmodified faces, which were determined to match the average distance relationships found in a sample of faces drawn from the same population. Long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 41 publications
6
35
1
Order By: Relevance
“…In contrast to the infancy literature which suggests that infants demonstrate more advanced processing of faces, such as processing based on second-order relations (Bhatt, et al, 2005;Thompson, et al, 2001) and prototype formation (de Haan, et al, 2001;Walton & Bower, 1993), research with children suggests that they have poor face recognition skills (Brace, et al, 2001;Mondloch, et al, 2006). Brace, et al (2001) concluded that some children between the ages of 2 and 4 years used featural rather than configural processing of faces based on their failure to show the inversion effect and faster response times to recognize inverted faces over upright faces within a storybook format.…”
Section: Storybook Formatmentioning
confidence: 67%
See 4 more Smart Citations
“…In contrast to the infancy literature which suggests that infants demonstrate more advanced processing of faces, such as processing based on second-order relations (Bhatt, et al, 2005;Thompson, et al, 2001) and prototype formation (de Haan, et al, 2001;Walton & Bower, 1993), research with children suggests that they have poor face recognition skills (Brace, et al, 2001;Mondloch, et al, 2006). Brace, et al (2001) concluded that some children between the ages of 2 and 4 years used featural rather than configural processing of faces based on their failure to show the inversion effect and faster response times to recognize inverted faces over upright faces within a storybook format.…”
Section: Storybook Formatmentioning
confidence: 67%
“…Research suggests that infants learn to discriminate and process faces very early in postnatal development Pascalis & de Schonen, 1994;Turati, et al, 2006). Infants demonstrate abilities to process faces on the basis of first- (Goren, et al, 1975;Simion, et al, 2002) and second-order relations (Bhatt, et al, 2005;Thompson, et al, 2001), as well as holistic information (Cohen & Cashon, 2001;Schwarzer, et al, 2007). These findings, as demonstrated through habituation, VPC, and novelty preference procedures, suggest that the development of face expertise emerges rapidly across the first year of postnatal life.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations